2016
DOI: 10.1590/s1980-65742016000100007
|View full text |Cite
|
Sign up to set email alerts
|

Reference index and reduction in physical fitness tests proposed by PROESP-BR

Abstract: The purpose of this study was to create an unifying index of the PROESP-BR tests for school aged teenagers and propose a reduction in the physical fitness tests. A total of 414 adolescents between the ages of 15 and 17 years old, representative of the public school population in the city of Cuiaba were evaluated. The tests include general physical fitness, proposed by PROESP-BR. Multivariate factorial analysis was used, observing the commonality/ representativeness of each test with regard to the set, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…Regarding the location of these studies, it was identified that the Southern and Southeastern regions of Brazil were those that most published articles on MS in children and adolescents, with 18 studies 7-9,12-27 . Regarding the design of included studies, 22 had cross-sectional 3,7-9,14-21, [23][24][25][27][28][29][30][31][32][33][34][35] and five longitudinal design 12,13,22,26,36 (Table 1). The studies covered different primary goals as can be observed in Table 1; however, all of them performed MS measurements as defined in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding the location of these studies, it was identified that the Southern and Southeastern regions of Brazil were those that most published articles on MS in children and adolescents, with 18 studies 7-9,12-27 . Regarding the design of included studies, 22 had cross-sectional 3,7-9,14-21, [23][24][25][27][28][29][30][31][32][33][34][35] and five longitudinal design 12,13,22,26,36 (Table 1). The studies covered different primary goals as can be observed in Table 1; however, all of them performed MS measurements as defined in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Freitas et al, 35 Montes Claros, MG No study was classified with low methodological quality / high risk of bias. Moderate methodological quality/moderate risk of bias was verified in ten studies (37.0%) 7,12,13,15,19,21,23,26,28,29 , while seventeen studies … continue (67.0%) 3,8,9,14,16,17,20,22,24,25,27,[30][31][32][33]35,36 were classified with high methodological quality / low risk of bias (Table 2). MS was investigated in fourteen different ways.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations